2020
DOI: 10.1002/prep.201900291
|View full text |Cite
|
Sign up to set email alerts
|

Study of Initial Pressure Rise in Multi Grain Solid Propellant Rocket Motor

Abstract: In the present research, an experimental and numerical investigation has been performed to study initial pressure rise in multi grain solid rocket motor. A cluster of seven uninhibited tubular grains of double base propellant is analysed to get near neutral pressure in rocket motor. It is experimentally observed that in some static firings initial pressure rise in first 100 ms is higher than the predicted value of~7.5 MPa. The average pressure in the rocket motor is~7 MPa and total burning time of these grains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The maximum pressure of the internal surface of propellant grains is usually regarded as 4–10 MPa during ignition pressurization [1, 3, 4, 41]. Besides, previous research results showed that once a limit pressure referred to as the saturation pressure (pressure threshold) is exceeded, a further increase of pressure does not lead to a significantly increase in ultimate properties of the solid propellants [22].…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The maximum pressure of the internal surface of propellant grains is usually regarded as 4–10 MPa during ignition pressurization [1, 3, 4, 41]. Besides, previous research results showed that once a limit pressure referred to as the saturation pressure (pressure threshold) is exceeded, a further increase of pressure does not lead to a significantly increase in ultimate properties of the solid propellants [22].…”
Section: Experimental Methodologymentioning
confidence: 99%
“…All components are made from mild steel of IS-2062 grade. Various components of the rocket motor are shown in Figure 5 [26].…”
Section: Rocket Motor Componentsmentioning
confidence: 99%
“…In recent years, studies on the ignition process of solid rocket motors have achieved good results. Previous research content has included the ignition process characteristics of solid rocket motors with endburning grains [3,4], tube grains [5-9, 10, 11, 12, 13-16], multigrains [17][18][19], wing grains [13,20,21], and the influence of the opening pressure of the cover [3], the quality of the ignition powder [22,23,24], the initial temperature of the propellant [25] and other factors on the ignition process of the solid rocket motor. In terms of experiments, Kuo et al studied the flame propagation characteristics in the wing slot region of a small-scale rocket engine with a noninvasive optical diagnostic method [26].…”
Section: Introductionmentioning
confidence: 99%